The impact of the corona pandemic covid 19 on the economic situation of families, a study of the economic situation of the Algerian family in light of the spread of the corona pandemic - Omar HASSINI (Social Sciences Journal, 1970)
This research paper aimed to identify “the impact of the corona pandemic covid 19 on the economic situation of families، a study of the economic situation of the Algerian family in light of the spread of the corona pandemic.” The study focused on determining the reality of the economic situation in the Algerian family in light of the spread of the corona pandemic covid 19، and determining the effects of those The pandemic affected the economic situation in the Algerian family and in families that witness a decrease in their income through the differences in those repercussions that are due to the variables (the Corona pandemic،the economic situation).